EKSPLORASI KARYA SENI RUPA 3 DIMENSI BERBASIS LINGKUNGAN PADA MATA KULIAH SENI RUPA DAN KERAJINAN DI PGSD UST YOGYAKARTA - Poppy Indriyanti; Dyan Indah Purnama Sari (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study was to determine the process and creativity of Environmental-Based 3-Dimensional Artwork Exploration in the Arts and Crafts Course at PGSD UST Yogyakarta which was carried out by students during online learning. The work process starting from the selection of the main materials, the preparation of tools and supporting materials to the tutorial preparation process was carried out independently by each student but was still monitored through the online lecture process. This research used a qualitative method. To collect data, researchers used direct observation techniques, in-depth interviews, and documentation. The data analysis steps included data reduction, data presentation and verification, while the data validity test included internal validity, external validity, dependability and confirmability. This research had been running until the stage of data collection. For the next step, the researcher continued to complete more in-depth data collection in the form of documentation, other supporting documents and others stuffs for the preparation of the final report. The results of this study could be used as a source or reference material, both by policy makers, prospective elementary school teachers, students of elementary school teacher education study programs, academic practitioners and the community in learning arts, culture and crafts (SBDP). It is hoped that future elementary school teacher candidates can become facilitators and moderators in learning arts and culture and can utilize natural materials around their homes and schools in making artworks and crafts in elementary schools. Keywords: exploration, 3 dimensions, fine arts and crafts, environment, nature. References: Adi, S. 2013. Meningkatkan Kreatifitas Seni Rupa Anak Melaui Kegiatan Mencetak Dengan Bahan alam Di Paud Aisyiyah Lanso No Pesisir Selatan. SPEKTRUM PLS Vo.1, No. 2 Juli 2013. Padang: Program Studi Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Padang. Bahari, N. 2008. Kritik Seni : Wacana Apresiasi dan Kreasi. Yogyakarta: Pustaka Pelajar. Dharmawati. 2012. Materi Kuliah Kesenian dan Kerajinan. Yogyakarta: PGSD UST Faisal, S. 2007. Format-Format penelitian Sosial, Jakarta: Raja Grafindo Persada. Hendriani, D. 2016. Pengembangan Seni Budaya & Kerajinan. Yogyakarta: Ombak. Kemendikbud. 2020. Analisa karya Seni Rupa Tiga Dimensi, Modul Tema 15. Jakarta: Depdikbud. Makariem, N. 2020. Surat Edaran Mentri Pendidikan (Mendikbud) N0.4 Tahun 2020. Jakarta: Depdikbud. Mulyani, N. 2016. Pendidikan Seni Tari Anak Usia Dini. Yogyakarta: Gava Media. Mulyani, N. 2017. Pengembangan Seni Anak Usia Dini. Bandung: PT Remaja Rosdakarya. Moelong, L.J. 2000. Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya Offset Purwanto. 2016. Pendidikan karakter melalui Seni. Yogyakarta: Pustaka Pelajar. Pusdatin Kemendikbud. 2020. Asik Belajar Berkelompok Solusi Belajar di Kala Pandemi dengan Memanfaatkan Aplikasi Manajemen Proyek. pusdatin.kemdikbud.go.id. Raharjo, T. 2011. Seni Kriya dan Kerajinan. Yogyakarta: Program Pascasarjana ISI. Salim, E. 1983. Lingkungan Hidup dan Pembangunan. Jakarta: Mutiara. Setyaningrum, F. & Hutami, H.A. 2021. Pembentukan Kreativitas Melalui Pembelajaran Sbdp Kelas IV Pada Materi Melukis Di SD Muhammadiyah Condongcatur. Jurnal Taman Cendikia Vol.05 No. 01 Juni 2021 Sugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&B. Bandung: Alfabeta. Suhaya. 2016. Pendidikan Seni Sebagai Penunjang Kreatifitas. Jurnal Pendidikan Dan Kajian Seni, Vol. 1, No.1, April 2016. Banten: Fakulitas Keguruan Ilmu Pendidikan Universitas Sultan Ageng Tirtayasa Soedewi, S. 2007. Teknik dan Ragam Hias Batik. Yogyakarta: Paguyuban pecinta Batik Indonesia Sekarjagad.